RANCANG BANGUN SISTEM INFORMASI MONITORING PENGELOLAAN SAMPAH TPS 3R MENGGUNAKAN CODEIGNITER - I Gusti Ngurah Agung Pawana P.; Made Widya Jayantari; I Nyoman Arnawan (Jurnal Pendidikan Teknologi dan Kejuruan, 2026)
Waste management at Reduce, Reuse, Recycle Waste Processing Sites (TPS 3R) plays an important role in supporting community-based waste reduction. However, the operations of the TPS 3R in Bedulu Village still face issues in recording and monitoring waste management activities, which are mostly done manually. These conditions have the potential to cause recording errors, delayed reporting, and low transparency in data on waste volume and economic transactions. This research aims to design and develop a web-based waste management monitoring information system that integrates waste data, users, and operational transactions of 3R TPS in a structured, real-time manner. The research method used is Research and Development (R&D) with stages of system needs analysis, software architecture design based on Model–View–Controller (MVC), implementation using the CodeIgniter framework and MySQL database, and system testing using the Black Box Testing method. The novelty of this research lies in the development of an integrated monitoring dashboard that combines waste volume data, waste type classification, and economic transactions into a single web-based operational information system for 3R TPS. The test results show that all system functions operate at 100% success, with no functional errors. The system can improve the efficiency of operational data recording, accelerate the report recapitulation process, and provide real-time data-monitoring visualization to support data-driven decision-making by TPS 3R managers.